RETRACTED : The Influence of Brand Image, Celebrity Endorser and Price Perception pn The Purchase Decision of Yamaha Mio Motorcycles - Nurwin Sjoekri; Hery Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research was aimed for knowing: (1) the influence of brand image towards buying decision of brand Yamaha Mio Motorcycle, (2) the influence of celebrity endorser towards buying decision of brand Yamaha Mio Motorcycle, (3) the influence of price perception towards buying decision of brand Yamaha Mio Motorcycle and (4) the influence of brand image, celebrity endorser and price perception towards buying decision of brand Yamaha Mio Motorcycle. This research used quantitative approach by applying survey method. This research used purposive sampling or took the samples based on specific characteristics. The samples of this research were 100 buyers of Yamaha Mio Motorcycle Branch Tanah Kusir Jakarta. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis techniques used to answer the hypothesis is multiple regression. Yamaha is expected to keep attention to the level of consumer confidence in selebiriti as representative of Yamaha Mio. To increase consumer confidence for example by increasing the use of celebrities who have credibility and high popularity and favored by many consumers, so that later will form a good image in the minds of consumers of the product and make purchasing decisions.